2019
DOI: 10.21873/invivo.11780
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Implication of Pre-operative C-reactive Protein-Albumin Ratio as a Prognostic Factor of Patients With Pancreatic Ductal Adenocarcinoma: A Single-institutional Retrospective Study

Abstract: Background: The C-reactive protein (CRP)-toserum albumin ratio is associated with a poor prognosis in patients with several cancers. The purpose of this study was to clarify the relationship between the preoperative CRP/Alb ratio and overall survival of pancreatic ductal adenocarcinoma (PDAC) in patients who received radical surgery and S-1 adjuvant chemotherapy. Patients and Methods: We included 117 patients who underwent radical surgery with S-1 adjuvant chemotherapy. We constructed receiver operating charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 19 publications
(8 reference statements)
0
24
0
Order By: Relevance
“…A further 14 studies were excluded, as 5 were single-arm studies, 2 evaluated postoperative values, and the remaining 7 included patients who did not have pancreatic cancer resection. Therefore, 8 retrospective comparative studies [20][21][22][23][24][25][26][27] were deemed appropriate for inclusion (Figure 1). The included studies reported a total of 1056 patients undergoing pancreatic cancer resection, of whom 378 belonged to the high CAR group and the remaining 678 belonged to the low CAR group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A further 14 studies were excluded, as 5 were single-arm studies, 2 evaluated postoperative values, and the remaining 7 included patients who did not have pancreatic cancer resection. Therefore, 8 retrospective comparative studies [20][21][22][23][24][25][26][27] were deemed appropriate for inclusion (Figure 1). The included studies reported a total of 1056 patients undergoing pancreatic cancer resection, of whom 378 belonged to the high CAR group and the remaining 678 belonged to the low CAR group.…”
Section: Resultsmentioning
confidence: 99%
“…Murakawa [22] • A total of 117 patients with resectable PDAC were included who had radiacal surgery with S1 adjuvant chemotherapy.…”
mentioning
confidence: 99%
“…Many studies have also reported that GPS plays a pivotal role in the progression of various malignancies, and is closely related to poor prognosis in patients [ 22 , 23 , 24 , 25 , 26 ]. In recent years, CAR has also been reported to have clinical implications and usefulness in many studies, including research regarding pancreatic cancer [ 27 , 28 , 29 , 30 , 31 ]. Cancer patients have chronically increased Interleukin-6 (IL-6) in the circulating blood, affecting the acute-phase proteins (APPs); positive APP corresponds to CRP, and negative APP to albumin.…”
Section: Discussionmentioning
confidence: 99%
“…A growing number of studies have shown an association between plasma albumin concentrations, inflammation, and tumorigenesis ( 18 , 19 ). Available evidence suggests that hypoproteinemia is strongly associated with poor quality of life in cancer patients and is associated with poor prognosis in patients with various malignancies ( 20 , 21 ). High fibrinogen and low albumin are associated with poor prognosis in cancer patients ( 12 , 22 ).…”
Section: Introductionmentioning
confidence: 99%